It starts with passion : do what you love and love what you do - Abraham, Keith (Be your best (Wiley (Firm)), 2019)
Bring more energy to everything in your life. It Starts with Passion will help you ignite the purpose in your life, as well as in the lives of your colleagues, employees, and associates. In-depth research, practical concepts, inspirational stories, and clear visual models will show you how to find out what's meaningful to you and pursue it with passion. For three decades, Keith Abraham has been helping people around the world to harnass their passion, achieve their goals and focus on what's most important to bring the best out of themselves and their business. It's time to embark on a life of certainty, clarity and confidence and It Starts with Passion. Originally published in 2013, this book has been reviewed and redesigned to become part of the Wiley Be Your Best series - aimed at helping readers acheive professional and personal success.